From Mouth to Brain: Distinct Supragingival Plaque Microbiota Composition in Cerebral Palsy Children With Caries - Liu, Mingxiao; Shi, Yuhan; Wu, Kaibin; Xie, Wei; Ser, Hooi-Leng; Jiang, Qianzhou; Wu, Lihong (Frontiers in Cellular and Infection Microbiology, 2022)
Children with cerebral palsy (CP) present a higher prevalence and severity of caries. Although researchers have studied multiple risk factors for caries in CP, the role of microorganisms in caries remains one of the critical factors worth exploring. In order to explore the differences in the supragingival plaque microbiota (SPM), supragingival plaque samples were collected from 55 CP children and 23 non-CP children for 16S rRNA sequencing. Distinct SPM composition was found between CP children with severe caries (CPCS) and non-CP children with severe caries (NCPCS). Further sub-analysis was also done to identify if there were any differences in SPM among CP children with different degrees of caries, namely caries-free (CPCF), mild to moderate (CPCM), and severe caries (CPCS). After selecting the top 15 most abundant species in all groups, we found that CPCS was significantly enriched for Fusobacterium nucleatum, Prevotella intermedia, Campylobacter rectus, Porphyromonas endodontalis, Catonella morbi, Alloprevotella tannerae, Parvimonas micra, Streptobacillus moniliformis, Porphyromonas canoris compared to NCPCS. By comparing CPCF, CPCM, and CPCS, we found that the core caries-associated microbiota in CP children included Prevotella, Alloprevotella, Actinomyces, Catonella, and Streptobacillus, while Capnocytophaga and Campylobacter were dental-health-associated microbiota in CP children. Alpha diversity analysis showed no significant difference between NCPCS and CPCS, but the latter had a much simpler core correlation network than NCPCS. Among CP children, CPCM and CPCF displayed lower bacterial diversity and simpler correlation networks than CPCS. In summary, the study showed the specific SPM characteristics of CPCS compared to NCPCS, revealed the core SPM in CP children with different severity of caries (CPCF, CPCM, and CPCS) and their correlation network. Hopefully, the study would shed light on better caries prevention and therapies for CP children. Findings from the current study offer exciting insights that warrant larger cohort studies inclusive of saliva and feces samples to investigate the potential pathogenic role of oral microbiota through the oral-gut-brain axis in CP children with caries.